Metabolic modulation of chromatin: implications for DNA repair and genomic integrity - Liu, Jinping; Kim, Jeongkyu; Oberdoerffer, Philipp (Frontiers in Genetics, 2013)
The maintenance of genomic integrity in response to DNA damage is tightly linked to controlled changes in the damage-proximal chromatin environment. Many of the chromatin modifying enzymes involved in DNA repair depend on metabolic intermediates as co-factors, suggesting that changes in cellular metabolism can have direct consequences for repair efficiency and ultimately, genome stability. Here we discuss how metabolites may contribute to DNA double-strand break (DSB) repair, and how alterations in cellular metabolism associated with both aging and tumorigenesis may affect the integrity of our genomes.